Aflatoxins and their Repercussions in Aquaculture: A Review - Deepa Bhatt; Abhed Pandey (Fishery Technology, 2022)
Fish consumption has been increasing globally, owing primarily to its availability, accessibility, and affordability in comparison to other types of meat consumption, such as beef, pork and poultry. The detection of mycotoxins in feeds and their constituents has gained popularity in aquaculture because of animal health losses caused mostly by the presence of aflatoxins in fish feed, consequently,various worries arise, particularly about the quality  of fish available on the market due to the possibility of presence of aflatoxin in fish meat. Residues of aflatoxins could be found in any animal-derived product, posing a financial risk as well as a risk to human and animal health. Aflatoxins also represent a serious source of contamination in foods and feeds in many different parts of the world. The toxin has been reported to cause heavy mortality in aquaculture. Various physical, chemical and methods are employed to  econtaminate the aflatoxins. In recent years, there has been a lot of talk about aflatoxins and their environmental effects in  quaculture.